A new Tb(iii)-functionalized layer-like Cd MOF as luminescent probe for high-selectively sensing of Cr3+. Issue 48 (28th November 2017) - Wang, Yi; Yang, Huan; Cheng, Gang; Wu, Yunying; Lin, Shaomin
Abstract : A new layer-like metal–organic framework [Cd4 (NDIC)4 ·5DMF·H2 O]DMF n (NDIC = 5-(5-norbonene-2, 3-dicarboximide) isophthalic acid) was synthesized by solvothermal method. Abstract : A new layer-like metal–organic framework [Cd4 (NDIC)4 ·5DMF·H2 O]DMF n (NDIC = 5-(5-norbonene-2, 3-dicarboximide) isophthalic acid) was synthesized by solvothermal method. It was used as a parent framework to encapsulate Tb 3+ cations in Cd-MOF. The obtained composite Tb(3+)@Cd-MOF exhibited excellent luminescence and produced a remarkable quenching effect in the luminescence emission of Tb 3+ upon the introduction of Cr 3+ . Subsequently, Tb(3+)@Cd-MOF was developed as a highly selective and sensitive probe for detection of Cr 3+ . In particular, the luminescence probe of Cr 3+ had a low detection limit (7.5 × 10 −8 M), a broad linear range (1 × 10 −7 –5 × 10 −6 M). A paper strip coated with Tb(3+)@Cd-MOF was also shown to be highly selective to Cr 3+ under the irradiation of 254 nm UV light of by the naked eyes. This is the first example for detecting metal ions based on a lanthanide functionalized new metal–organic framework (MOF).